Analysis of the incidence and factors predictive of inadvertent parathyroidectomy during thyroid surgery. Issue 7 (10th June 2016) - Hone, R W A; Tikka, T; Kaleva, A I; Hoey, A; Alexander, V; Balfour, A; Nixon, I J
Abstract: Background: Inadvertent (or incidental) parathyroidectomy can occur during thyroidectomy. However, the factors associated with inadvertent parathyroidectomy remain unclear. This study aimed to report the rate of inadvertent parathyroidectomy during thyroidectomy and associated risk factors. Methods: Variables including fine needle aspiration cytology findings, age, sex, thyroid weight, concurrent neck dissection, extent of thyroidectomy, and the presence of cancer and parathyroid tissue within the specimen were recorded for 266 patients. The incidence of post-operative hypocalcaemia was also recorded. Univariate and multivariate analysis were performed to identify factors associated with inadvertent parathyroidectomy. Results: The inadvertent parathyroidectomy rate was 16 per cent. Univariate analysis revealed that cancer and concurrent neck dissection predicted inadvertent parathyroidectomy. On multivariate analysis, only concurrent neck dissection remained an independent predictor of inadvertent parathyroidectomy: it was associated with a fourfold increase in inadvertent parathyroidectomy. Conclusion: The inadvertent parathyroidectomy rate was 16 per cent and concurrent neck dissection was identified as an independent predictor of inadvertent parathyroidectomy.